Introductory forest science - Ratnasingam, Jegatheswaran (Universiti Putra Malaysia Press, 2014)
This book is an attempt to present the complete array of subject matters involved in the study of forestry science in an single volume. prepared specifically for the first-year undergraduates in forestry curriculum throughout Malaysia and region, it will also find acceptance among all those interested in the forest and its resources.